(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
This research aims to: to know, understand and expose the virtues of the formation of good behavioral personality and methods used in the formation of good behavior personality of children in early marriage family environment in Lubuk Besar Sub-District bangka tengah regency. As for finding solutions to the above problems researchers use the following methodology: in this study researchers used a qualitative approach to phenomenology is to observe social symptoms, and the role of each individual to educate children and families in each member of society. Because every education has a purpose to build a good behavior, there is a pattern of empathy and a role that contains and implements educational values or that every family has the right to educate and be responsible for educating children and their families. The main informants in this study are the key informants in this study are Islamic Religious Education teachers and landfill teachers and the informants in this study are families and children of early marriage perpetrators, then for the supporting informants are the sub-district staff of Lubuk Besar to look for data on the general picture of Lubuk Besar Sub-District. And the data collection techniques in this study are: observation techniques, interviews and documentation. Then the analysis techniques that researchers use are: data reduction, data presentation and data verivcation. The result of this study is that the first, the formation of personality akhlakul kaimah in the early marriage family environment does not go the maximum, because the family as the person shaper of the child does not have enough provision in building a household so that parents who are married early have not been able to apply everything that is the responsibility as a parent in educating and raising the child. Second, as a large number of children have poor adab and morals and some children born to early married parents have physical and psychological disabilities such as being born in un-normal circumstances. Third, among parents who are married early already married two to three times due to various domestic conflicts that occur in early marriage families caused by the economy, as well as other problems. Fourth, most parents who marry early are more entrusted to teachers whether school teachers or teachers where their children learn to pay in providing religious education to the Fifth child, the causative factor of early marriage in Lubuk Besar Subdistrict is mainly due to economic, educational, parental factors and free associations that are stuck with the wrong courtship style. Although in Islam there is no age limit when a person will marry, but early marriage is highly discouraged because it will be fatal in either the home life or the child of an early marriage perpetrator if not provided with sufficient knowledge in educating children and households. Sixth, the average observer is an early marriage and a housewife. Seventh, the adverse effects of early marriage in Lubuk Besar sub-district include depression (crazy), not being able to take care of children, family conflict, early divorce, economic pressures, family disharmony, risky pregnancies, the head of the family difficulty finding work due to the lack of experience before marriage. Thus it is highly discouraged for today’s young people to perform underage marriages. Because it will not only affect him and his family but also on the children of early marriage abusers who will become the next generation of the nation.